2020
DOI: 10.5194/amt-13-4159-2020
|View full text |Cite
|
Sign up to set email alerts
|

A compact, high-purity source of HONO validated by Fourier transform infrared and thermal-dissociation cavity ring-down spectroscopy

Abstract: Abstract. A well-characterized source of nitrous acid vapour (HONO) is essential for accurate ambient air measurements by instruments requiring external calibration. In this work, a compact HONO source is described in which gas streams containing dilute concentrations of HONO are generated by flowing hydrochloric acid (HCl) vapour emanating from a permeation tube over continuously agitated dry sodium nitrite (NaNO2) heated to 50 ∘C. Mixing ratios of HONO and potential by-products including NO, NO2, and nitrosy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 27 publications
(48 reference statements)
0
21
0
Order By: Relevance
“…environments, with levels up to 50 ppbv reported from gas stove cooking emissions (Collins et al, 2018;Gligorovski, 2016;Gómez Alvarez et al, 2012;Liu et al, 2019;Young et al, 2019;Zhou et al, 2018). There are a number of atmospheric HONO sources that have been reported: direct emissions (e.g., vehicles and biomass burning), gas-phase homogenous reaction of NO and OH, biological production in soils (Mushinski et al, 2019), and a number of heterogeneous surface reactions (Spataro and Ianniello, 2014, and references therein).…”
Section: Introductionmentioning
confidence: 99%
“…environments, with levels up to 50 ppbv reported from gas stove cooking emissions (Collins et al, 2018;Gligorovski, 2016;Gómez Alvarez et al, 2012;Liu et al, 2019;Young et al, 2019;Zhou et al, 2018). There are a number of atmospheric HONO sources that have been reported: direct emissions (e.g., vehicles and biomass burning), gas-phase homogenous reaction of NO and OH, biological production in soils (Mushinski et al, 2019), and a number of heterogeneous surface reactions (Spataro and Ianniello, 2014, and references therein).…”
Section: Introductionmentioning
confidence: 99%
“…This method requires the reaction chamber to be heated to 50 • C and can produce mixing ratios of HONO over a wide range (5-20 000 ppb) (Febo et al, 1995) that often require large dilution flows to reach typical outdoor atmospheric concentrations (Lao et al, 2020). Furthermore, the high HONO mixing ratios produced by this approach can disproportionate to form NO and NO 2 (Febo et al, 1995;Stutz et al, 2000;Gingerysty and Osthoff, 2020;Lao et al, 2020). As a result, this method typically requires an additional technique to verify both the purity and output concentration of HONO (Pérez et al, 2007;Gingerysty and Osthoff, 2020).…”
Section: Instrument Calibrationmentioning
confidence: 99%
“…Elevated concentrations of HONO indoors are rele-vant not only due to the adverse health effects caused by inhalation (Beckett et al, 1995;van Strien et al, 2004;Jarvis et al, 2005), but also due to the potential for OH production indoors from HONO photolysis. OH concentrations were thought to be negligible indoors due to reduced light intensity, especially at short wavelengths and lower ozone mixing ratios, but several studies have indicated that photolysis of elevated indoor HONO can produce OH concentrations similar to those found outdoors, even at reduced photolysis frequencies (Gómez Alvarez et al, 2013;Bartolomei et al, 2015;Kowal et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the high HONO mixing ratios produced by this approach can disproportionate to form impurities such as NO and NO2 (Febo et al, 1995;Stutz et al, 2000;Gingerysty and Osthoff, 2020;Lao et al, 2020), and excessive amounts of HCl can result in the production of ClNO (Pérez et al, 2007;Gingerysty and Osthoff, 2020). As a result, this method typically requires an additional technique to verify both the purity and output concentration of HONO (Pérez et al, 2007;Gingerysty and Osthoff, 2020). While appropriate for a laboratory setting, these limitations, along with the long warmup times needed to ensure stability, can make this method less suitable for calibration in a field setting.…”
Section: Instrument Calibrationmentioning
confidence: 99%
“…In addition to improving the sensitivity of the instrument and testing for potential interferences, future work will involve improving the stability of the beam overlap in order to improve the precision associated with the photofragmentation efficiency calibration method described above. In addition, the measured HONO sensitivity by the photofragmentation calibration method will be compared to that determined through the production of HONO by the reaction of gas-phase hydrochloric acid in a humidified gas stream with solid sodium nitrite (Febo et al, 1995;Gingerysty and Osthoff, 2020;Lao et al, 2020). While this calibration method is not as simple to implement in the field in addition to requiring quantification of the HONO produced, comparison of the instrument sensitivity derived from this calibration source in the laboratory would provide additional confidence in the calibration of the instrument by the photofragmentation method.…”
Section: Measurements Of the [Hono]/[oh]mentioning
confidence: 99%